Upaya Guru Agama Dalam Menanggulangi Kenakalan Siswa (Studi Kasus Di MTs. Al-Ikhlas Braja Sakti Lampung Timur) - Fresyam Antika Ajeng (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2023)
Student delinquency is a particular concern in the world of education today, because this has a serious impact on students' personal development and even has an impact on society. This delinquency is an anti-social act that violates applicable law, carried out by someone who is approaching adulthood and if it is carried out by an adult it will qualify as a crime. Various delinquencies committed by students have had a negative impact not only on the students themselves, the news circulating can be detrimental to the school which is often exposed to verbal abuse, it is not uncommon for public interest to assume that the low quality, behavior/personality of students is a lack of ability of the school to control the student's psychology. This research was conducted to determine the forms of student delinquency, the factors that influence student delinquency and the school's efforts to overcome student delinquency at Madrasah Tsanawiyah Al-Ikhlas Braja Sakti, East Lampung Regency. This research is a qualitative descriptive research, namely by describing and analyzing in-depth research results and then drawing conclusions. Data was obtained by conducting observations, in-depth interviews and documentation studies. Factors that influence student delinquency are caused by lack of attention from parents (broken home), influence from peers, and also from students themselves because they are lazy and afraid of teachers. The school's efforts to overcome/overcome student delinquency include collaborating with parents and the community, and also providing educational punishments to deter students and making a commitment to all teachers to always remind every student who commits any form of violation.